2022
DOI: 10.1155/2022/8755464
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive and Selective Electrochemical Detection of Dopamine Based on CuO/PVA Nanocomposite-Modified GC Electrode

Abstract: At present, the determination of dopamine (DA) is enormously necessary for the human body. Since then, it has played a crucial role in the brain that affects mood, sleep, memory, learning, and concentration. Dopamine insufficiency is a threat to human health. Dopamine recognition is important to avoid this problem. Copper oxide (CuO) nanoparticles are one of the potentials which can be used in the detection of dopamine level in the sample. In this work, CuO was synthesized by a simple chemical precipitation te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Electron microscopy methods are a key to determining the shape of polymeric nanoparticles and other objects whose toxicity may be determined by their form [ 16 ].…”
Section: Characterization Of Nanoparticlesmentioning
confidence: 99%
“…Electron microscopy methods are a key to determining the shape of polymeric nanoparticles and other objects whose toxicity may be determined by their form [ 16 ].…”
Section: Characterization Of Nanoparticlesmentioning
confidence: 99%
“…The experiment was repeated three times for maintaining triplicates. The readings were taken in three different fixed directions for each replicate, and the average values were noted [11].…”
Section: Characterization Of Silvermentioning
confidence: 99%
“…Among them, copper oxide (CuO) NPs prove to be excellent candidates for dopamine detection due to their useful properties such as better thermal conductivity, high temperature superconductivity, low toxicity, chemical stability, good catalytic behavior, small bandgap, spin dynamics, and simplicity in synthesis process [33]. So far, many chemical and physical methods with different morphologies, particle sizes, and surface areas have been practiced for the synthesis of CuO NPs, and their further utilization in the field of dopamine sensors [34], [35], [36]. For instance, a bio-electrochemical sensing approach was employed using CuO NPs-decorated graphene oxide sheets to detect dopamine [34].…”
Section: Introductionmentioning
confidence: 99%
“…The fabricated dopamine sensor reported a high sensitivity of 0.806 µA/µM over a broad linear range of 0.25 -17 µM with a LOD as 2.6 nM. Recently, Azharudeen et al reported an ultrasensitive and selective electrochemical detection of dopamine based on CuO NPs and polyvinyl alcohol (PVA) nanocomposite-modified electrode [35]. CuO NPs were modified with PVA as a capping agent to sense dopamine with a maximum sensitivity of 183.12 µA mM -1 cm -2 and a detection limit of 0.017 µM.…”
Section: Introductionmentioning
confidence: 99%